Time or Space? Relative Importance of Geographic Distribution and Interannual Variation in Three Lineages of the Ascidian Pyura chilensis in the Southeast Pacific Coast - Haye, Pilar A.; Turon, Xavier; Segovia, Nicolás I. (Frontiers in Marine Science, 2021)
Spatial and temporal variation of environmental parameters can affect dispersal, recruitment and population persistence of marine benthic species. Studies including inter-annual comparisons of genetic structure often indicate high/moderate temporal heterogeneity in marine invertebrates, which may be a prevailing pattern. This suggests that temporal studies are necessary to understand the dynamics of marine metapopulations. In this study, we analyzed the spatio-temporal genetic structure of the ascidian Pyura chilensis, a low dispersal sessile marine species endemic from the Southeast Pacific coast and highly demanded for human consumption. We sequenced a fragment of the mitochondrial gene Cytochrome Oxidase I (COI) from 1,005 individuals of six locations (30–40 individuals per site and year) spanning a wide latitudinal range (24°–42°S) and sampled over 5 years (2012, 2014, 2015, 2016, and 2017). The genetic structure of COI indicates the presence of three monophyletic lineages (haplogroups 1–3) previously described for the species, being one of them highly divergent and geographically restricted ( 39°S, Los Molinos). Considering the whole dataset, a picture of strong spatial differentiation but temporal stability emerged in Pyura chilensis. However, detailed studies of the two main lineages revealed important differences in the extent of spatio-temporal variation. Analyses using haplotype frequencies sorted by site and year showed that, for haplogroup 1, genetic variation was explained mainly by differences between sites, while for haplogroup 2 differences between years were prevailing. Haplogroup 3 was restricted to the most southern sites, and also showed inter-annual variability in its frequency. These results point to disparate patterns of genetic differentiation, which may reflect different adaptive scope or variation in reproductive and dispersal features and could be a response to extreme events such as El Niño (2015–2016). This work calls for caution when obtaining general trends in species clearly differentiated in lineages, and prompts instead for separate analyses of sub-specific genetic lineages whenever possible.